Sedmikrásky - Sust, Jiří, 1919-1995; Šlitr, Jiří, 1924-1969; Mareš, Karel (Eclipse (Criterion Collection (Firm)). Pearls of the Czech new wave., 2012)
Sedmikrasky (Daisies): Two teenage girls decide that since the world is spoiled they will be spoiled as well; accordingly they embark on a series of destructive pranks in which they consume and destroy the world about them.